Optical properties of nitride-rich SiNx and its use in CMOS-compatible near-UV Bragg filter fabrication - Reinoud F. Wolffenbuttel; Declan Winship; Yutao Qin; Yogesh Gianchandani; David Bilby; Jaco H. Visser (Optical Materials: X)
Nitride-rich silicon-nitride (SiNx) is being explored for its potential as a suitable optical material for use in microsystems operating in the near-UV spectral range. Although silicon-rich SiNx is widely accepted as a CMOS-compatible dielectric and micromechanical material, its optical absorption limits application to the visible to near-IR spectral range. However, this work shows that a balance can be achieved between a sufficiently high index of refraction (n> 2) and an acceptable optical loss (k<10−3) in nitride-rich SiNx of appropriate composition (x∼1.45). Bragg reflectors with a design wavelength at λo= 330 nm are used for validation. PECVD is used for sample preparation and experiments confirm that the spectral range available for use of SiNx-based optical microsystems extends to wavelengths as low as 300 nm.